County Kilkenny, Republik Ireland: Geomagnetische Prospektion auf dem eisenzeitlichen Hillfort „Freestone Hill“ - Rassmann, Knut; Voß, Hans-Ulrich (e-Forschungsberichte des DAI, 2023)
Subsequent to his exile in Britain as a result of the Nazi regime and his reinstatement in 1950 as the director of the Romano-Germanic Commission, Gerhard Bersu organized and directed excavations at the Iron Age hillfort of „Freestone Hill“ east of Kilkenny, Ireland. Geomagnetic surveys of the hill and its surroundings conducted in June 2014 provided further insights into the location and preservation of the site‘s fortifications as well as the uses to which its interior space and adjacent outlying areas were put. Freestone Hill provides an excellent opportunity to investigate the development of a region which was particularly favourable in the 4th century AD in terms of its geographical position and landscape. Moreover, the recent work also enables researchers to keep tabs on the presence of any potential Roman influences which might have been involved in the development of the hillfort.